Pengaruh Terapi Musik untuk Mengurangi Kecemasan Anak: Systematic Review - Novita Marcelina Kana Wadu; Henny Suzana Mediani (Jurnal Ilmu Keperawatan Anak, 2021)
Background – Anxiety is a common problem that often occurs in children during procedural treatment in the hospitals. Children’s emotional of response to procedural stress and anxiety may increase distress and influence to children recovery. One of the easy, safe and inexpensive efforts to reduce children's anxiety is through music therapy. Music can make a more positive mood and make coping and emotional wellbeing for children to reduce anxiety. However, there are no existing reviews dedicated to elucidating the effect of music interventions in reducing children’s anxiety. Purpose – To determine the effect of music therapy on children's anxiety. Design/methodology/approach – The research was a systematic review of randomized controlled studies. A comprehensive search strategy was performed using key databases such as PubMed / NCBI, DOAJ, and Science Direct to obtain relevant studies. Data is extracted and checked by reviewers. Each study was assessed based on 4 quality indicators which were adapted from the Cochrane Handbook for a systematic review with guidelines from PRISMA. Findings – 6 randomized control trial articles that met the inclusion and exclusion criteria and the eligibility criteria were obtained. This article shows that the effects of music therapy are statistically proven to be effective and significantly reduce children's anxiety. Listening to music can be used as a potential nursing intervention to relieve anxiety and can be a practical approach to dealing with anxiety and fear in children by paying attention to the type of music that will be given to children. Conclusion and recommendation – Music therapy was effective as a safe intervention in reducing anxiety in children undergoing medical and dental procedures. Music therapy can be considered as an additional non-pharmacological intervention in dealing with clinical situations that cause anxiety in children. Further research is recommended to determine the age of children who will most effectively and benefit from musical interventions during medical procedures.